Symposium on Muslims in Europe: The Institute for Comparative Social Research and the Haus der Kulturen der Welt, Berlin, Germany Rajab 3-5; 1412/ February 6-8, 1992 (American Journal of Islam and Society, 1992)
The question of a Muslim minority in the Western context has become animportant one in view of some h-and-hysteria literatu~th at continues to depictthis minority as a threat to Western liberal values and sociopolitical systems.The conference papers were structured around a basic theme of “Muslims, Islam,and Diaspora,” which reveals the difficulty of European scholars as well asgovernment officials in accurately conceptualizing the Muslim experience ofimmigration in the West.To be sure, there is no concept of an eschatological ”promised land” or “holyland” in the Qur’an to suggest “diaspora” - the dispersion of its adherents fromit - even in the remotest sense of the term. The entire earth, according to theQur’an, belongs to God and has been created for humanity to seek its ownadvancement towards the moral and spiritual goals wherever it so chooses, aslong as no injustices are committed against fellow humans beings. The conceptof dZir al hijrah, on the other hand, captures the spirit of Muslim emigrationto the West. It is a journey undertaken to overcome spiritual and moral“homelessness,” a physical transferral to the sphere which holds out the promiseof deviatiog the unfavorable conditions prevalent in one’s awn place of domicile.To this early meaning of emigration (hijrah) of a person from a particular placeor set of surroundings to seek protection is added emigration for the sake ofeconomic advantage, either temporanly or permanently, somewhere else. In otherwords, for Muslims this sphere of emigration is not what Europe wants toperceive, namely, a “diaspora” that would make them endeavor to return fromthe “diaspora” to their “holy land” located somewhere in Arabia.Apart from this lack of conceptual clarity in categorizing the Muslims’perception of their spatial relationship in the West, European scholars andadministrators are faced with another difficulty. This was discussed by ReinhardSchulze following his paper on ”International Organization and Muslims inEurope.” Schulze pointed out the inadequacy with which Europe defines the word“religion” and then imposes it on Islam, expecting to discover a central Islamic“church” headed by a Muslim “bishop” with whom the government can establishadministrative relations. Even more difficult for homogenous European nationslike France, where the majority is Catholic, is to recognize the existence of other“religions“ besides Christianity for administrative purposes. This difficulty isself-created, because such recognition entails empowering the followers of other ...